Using simulation to estimate parameters and reliability function for extreme value distribution - Akram, Makki (Journal of Economics and Administrative Sciences, 2010)
This study includes Estimating scale parameter, location parameter and reliability function for Extreme Value (EXV) distribution by two methods, namely: - - Maximum Likelihood Method (MLE). - Probability Weighted Moments Method (PWM). Used simulations to generate the required samples to estimate the parameters and reliability function of different sizes(n=10,25,50,100) , and give real values for the parameters are and , replicate the simulation experiments (RP=1000), and estimated the function reliability at two times (T=2,5), adopted mean square error for comparison between the results of estimators , and summarized all the results in tables especially prepared for this purpose, An analysis of the results in the tables it becomes that:- Estimators of (MLE) better than estimators of (PWM) in most of the cases studied in this research.